Thigh Compartment Syndrome, Presentation and Complications - Eric G. Verwiebe; Enes M. Kanlic; Jeremy Saller; Amr Abdelgawad (Biomolecules & Biomedicine, 2009)
To describe the patient population, etiology, and complications associated with thigh compartment syndrome (TCS). TCS is a rare (0.3% of trauma patients) condition of elevated pressure within a constrained space that may cause necrosis of all tissues within the compartment resulting in severe local (infection, amputation) and systemic complications (renal insufficiency, even death). Retrospective cohort This study examines the course of treatment of nine consecutive patients with thigh compartment syndrome sustained during an eight-year period at our Level 1 trauma centre, admitting more than 2,000 trauma patients yearly.